Pengembangan Media Pembelajaran Bahasa Inggris Flash Card Comic Kelas IV SDN 060872 Medan - Angeleva Revi Christa Sinaga; Dody Feliks Pandimun Ambarita; Lala Jelita Ananda; Albert Pauli Sirait; Tiarnita Maria Sarjani Br. Siregar; Charles Fransiscus Ambarita (Jurnal Tematik, 2025)
This research aims to determine the feasibility, practicality, and effectiveness of Flash Card Comic learning media for "Greetings and Leave Taking" material in Grade IV at SDN 060872 Medan. This study utilizes the Research and Development (R&D) method following the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this research include media experts, material experts, educational practitioners, and 20 fourth-grade students. The object of the research is the Flash Card Comic media, designed to improve students' understanding of English greetings and farewell expressions. The results of the study indicate that in terms of feasibility, the media obtained a score of 81.81% from media experts ("Feasible" category) and 93.3% from material experts ("Highly Feasible" category). In terms of practicality, questionnaire results showed that the media was rated as "Highly Practical" by educational practitioners. Regarding effectiveness, based on a comparison of pre-test and post-test scores, there was an increase in the average score from 39.75% to 73.75%. Based on an N-Gain analysis of 57.18%, the Flash Card Comic media is categorized as "Effective" in improving student learning outcomes.